PARTISIPASI MASYARAKAT PESISIR DALAM KONSERVASI HUTAN MANGROVE DI KECAMATAN PASEKAN KABUPATEN INDRAMAYU - , SYUKRON MA'MUN, Dr. Sri Rum Givarsih, S.Si., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Recently a lot of mangrove forest damaged because of the land use conversion from forest area to fish pond. Considering the function of mangrove forest is very important, there should be conservation. This research was conducted for some objectives